Selection of parameters of throttle hydraulic motor of electric hydraulic follow-up drive with controlled effort at output organ - Deribo, O. V. (Visnyk of Vinnytsia Politechnical Institute, 2010)
Technique aimed at determination of basic parameters of throttle hydraulic motor of electrohydraulic follow-up drive for the case when this drive must provide power impact on object of loading in the form of combination of constant component and monoharmonic oscillations of power with preset range of frequencies and amplitudes is suggested. Technique allows to provide desired loading law with minimum expenditure of energy produced by hydraulic power station.